Association between obesity and the risk of gastric cancer in premenopausal and postmenopausal women: A nationwide cohort study. Issue 10 (6th June 2021) - Choi, In Young; Choi, Yoon Jin; Shin, Dong Wook; Han, Kyung Do; Jeon, Keun Hye; Jeong, Su‐Min; Yoo, Jung Eun
Abstract: Background and Aim: Obesity was suggested to increase the incidence of gastric cancer (GC) in women, but results from previous studies were inconsistent. We investigated the relationship between obesity and the risk of GC according to menopausal status. Methods: We enrolled 1 418 180 premenopausal and 4 854 187 postmenopausal women aged ≥ 40 years using the Korean National Health Insurance System Cohort (2009–2014). We calculated hazard ratios (HRs) and 95% confidence intervals (CIs) for GC incidence according to body mass index (BMI) and waist circumference (WC) using the Cox proportional hazards models. Results: During the mean follow‐up period of 7.2 years, 42 441 women were newly diagnosed with GC. Compared with the group with BMI 18.5–22.9 kg/m 2, the adjusted HRs (95% CIs) for GC in the groups with BMI < 18.5, 23–24.9, 25–29.9, and ≥ 30 kg/m 2 were 1.12 (0.95–1.33), 0.96 (0.89–1.04), 1.02 (0.94–1.11), and 0.99 (0.83–1.18), respectively, for premenopausal women and 1.07 (1.00–1.14), 1.01 (0.99–1.04), 1.03 (1.00–1.05), and 1.11 (1.10–1.16), respectively, for postmenopausal women. Compared with the group with WC 65–74.9 cm, the adjusted HRs (95% CIs) for GC for the groups with WC < 65, 75–84.9, 85–94.9, and ≥ 90 cm were 1.00 (0.88–1.15), 1.03 (0.96–1.11), 1.10 (0.99–1.22), and 1.02 (0.81–1.27), respectively, for premenopausal women and 1.01 (0.94–1.09), 1.01 (0.99–1.04), 1.09 (1.06–1.13), and 1.14 (1.09–1.19), respectively, for postmenopausal women. Conclusions: We found a positive association between the highest BMI and WC category and risk of GC in postmenopausal women; however, such an association was not evident in premenopausal women.